1988
DOI: 10.1073/pnas.85.22.8713
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evidence for the existence of a dopamine- and cyclic AMP-regulated phosphoprotein (DARPP-32) in brown adipose tissue of pigs.

Abstract: The indirect immunofluorescence technique was used to study the cellular localization of DARPP-32, a dopamine-and cyclic AMP-regulated phosphoprotein, in brown adipose tissue of newborn piglets. Clusters of strongly DARPP-32-immunoreactive cells were found in brown adipose tissue from the interscapular area and around lymph nodes close to the kidneys, adrenal glands, descending aorta, and great veins in the neck. The DARPP-32-immunoreactive cells contained multilocular lipid droplets, had round, centrally loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…One explanation of these results is that PP1 in fully differentiated adipocytes is regulated by DARPP-32 binding, and stimulation of PP1 by insulin occurs through disinhibition of the phosphatase. Although DARPP-32 is considered to be the neuronal homologue of Inh-1, both pig brown fat and bovine adipose tissue have previously been reported to contain DARPP-32 (28,29). DARPP-32 immunoreactivity was also detected in primary rat adipocytes (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…One explanation of these results is that PP1 in fully differentiated adipocytes is regulated by DARPP-32 binding, and stimulation of PP1 by insulin occurs through disinhibition of the phosphatase. Although DARPP-32 is considered to be the neuronal homologue of Inh-1, both pig brown fat and bovine adipose tissue have previously been reported to contain DARPP-32 (28,29). DARPP-32 immunoreactivity was also detected in primary rat adipocytes (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…DARPP-32 expression is dramatically induced upon differentiation of 3T3-L1 fibroblasts into adipocytes and correlates with a decrease in PP1 basal activity and increase in stimulation by insulin. 3 Furthermore, DARPP-32 is expressed in pig brown fat (24), bovine adipose tissue (25), and in primary rat adipocytes, where it has been reported to be dephosphorylated in response to insulin (23). PP1 bound to PTG was resistant to inhibition by DARPP-32 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A role for dopamine in regulating the phosphorylation of DARPP-32 has been demonstrated in brain [22] and is postulated in the other tissues in which DARPP-32 is found [23]. It is likely that the phosphorylation of DARPP-32 in adipose tissue is also under catecholamine control, possibly by noradrenaline released from sympathetic nerve endings innervating the tissue and/or by other CAMPlinked neurotransmitters or hormones, such as insulin [8] or dopamine (see discussion in [7]). …”
Section: Sensitivity To Chemical Cleavagementioning
confidence: 99%
“…Recent studies have demonstrated DARPP-32 immunoreactivity in brown fat adipocytes from pig [7]. Moreover, inhibitor-1 , partially purified from rat adipose tissue, exhibited an apparent molecular mass of 32 kDa by SDSjPAGE [8].…”
mentioning
confidence: 99%